Simple Laboratory Test to Measure Damping Properties of Hardened Mortar or Concrete Elements - Faizah, Restu; Aminullah, Akhmad (International Journal of Sustainable Construction Engineering and Technology, 2020)
Concrete or mortar is the common material for earthquake resistant buildings in earthquake-prone areas. One of the crucial requirements of the earthquake resisting structure is the ability to reduce the earthquake energy as indicated by the damping ratio which can be upgraded by high damping materials. Currently, there are many researchers conducting damping properties investigation on several materials to improve the damping capacity of structures, but they are lack of literatures about the methodology of damping experiments. Therefore, this research aims to present a simple laboratory test to measure damping properties of mortar or concrete elements. It also presents the application of this method for a 100 x 100 x 500 mm3 mortar beam by two load variations (10 and 15 N) and five times loading for each variation. The result shows that the damping ratio of the mortar beam is 2.27% and 2.37% for 10 and 15 N load. Besides, it is known that the magnitude of the external forces also influences the damping ratio. This provides further research opportunities to improve the quality of testing methods. The experiment with more various loads and number of specimens to get the broader analysis is suggested.